Effects of Tributyrin on Intestinal Energy Status, Antioxidative Capacity and Immune Response to Lipopolysaccharide Challenge in Broilers - Jiaolong Li; Yongqing Hou; Dan Yi; Jun Zhang; Lei Wang; Hongyi Qiu; Binying Ding; Joshua Gong (Asian-Australasian Journal of Animal Sciences, 2015)
This study was carried out to investigate the effects of tributyrin (TB) on the growth performance, pro-inflammatory cytokines, intestinal morphology, energy status, disaccharidase activity, and antioxidative capacity of broilers challenged with lipopolysaccharide (LPS). A total of 160 one-day-old Cobb broilers were allocated to 1 of 4 treatments, with 4 replicated pens per treatment and 10 birds per pen. The experiment consisted of a 2×2 factorial arrangements of treatments with TB supplementation (0 or 500 mg/kg) and LPS challenge (0 or 500 μg/kg body weight [BW]). On days 22, 24, and 26 of the trial, broilers received an intraperitoneal administration of 500 μg/kg BW LPS or saline. Dietary TB showed no effect on growth performance. However, LPS challenge decreased the average daily gain of broilers from day 22 to day 26 of the trial. Dietary TB supplementation inhibited the increase of interleukin-1β (in the jejunum and ileum), interleukin-6 (in the duodenum and jejunum), and prostaglandin E2 (in the duodenum) of LPS-challenged broilers. Similar inhibitory effects of TB in the activities of total nitric oxide synthase (in the ileum) and inducible nitric oxide synthase (in the jejunum) were also observed in birds challenged with LPS. Additionally, TB supplementation mitigated the decrease of ileal adenosine triphosphate, adenosine diphosphate and total adenine nucleotide and the reduction of jejunal catalase activity induced by LPS. Taken together, these results suggest that the TB supplementation was able to reduce the release of pro-inflammatory cytokines and improve the energy status and anti-oxidative capacity in the small intestine of LPS-challenged broilers.